OVERCOMING FOREIGN LANGUAGE SPEAKING ANXIETY BY USING A LANGUAGE EXCHANGE WEBSITE IN ONLINE LEARNING - Emma Martina Pakpahan; Imeldawaty Gultom (PROJECT (Professional Journal of English Education), 2022)
The use of website in learning Foreign Language helps the students feel comfortable to speak. The objectives of the research is to investigate the Indonesian students’ self-rated degrees of their foreign language speaking anxiety (FLSA) and the effect of using language exchange website in online learning in overcoming the students’ FLSA. This study examined 100 undergraduate students of 4th and 6th semester majoring English education. Foreign Language Classroom Anxiety Scale (FLCAS) by Horwitz, Horwitz & Cope (1986) was adapted and distributed twice in the beginning of the class to find the state of speaking anxiety and in the end to see whether there is any significance effect after learning speaking by using a language exchange website. Finally, the six participants were chosen for interview. The interview was conducted to get more data about the foreign language speaking anxiety that they feel. It is found that the number of students who felt anxiety decreases after using language exchange website. Keywords:  Foreign Language, Speaking Anxiety, Language Exchange Website